Endovascular snare retrieval of an Angio‐Seal causing acute limb ischemia. Issue 12 (5th December 2021) - Busch, Lucas; Stern, Manuel; Wolff, Georg; Kelm, Malte
Abstract: Vascular complications (VCs) remain an important source of morbidity and mortality following percutaneous arterial catheterization. Vascular closure devices are popular and frequently used, but sometimes cause vessel occlusions that may require vascular surgery or complex endovascular procedures. In this case report, we describe the endovascular retrieval of an embolized Angio‐Seal device causing acute limb ischemia in a severely diseased 75‐year‐old female patient. This case highlights the endovascular technique using a snare catheter and adds another example to the growing evidence of an endovascular approach to manage vascular access site complications in comorbid patients at risk. Abstract : Snare catheter capture and retrieval of the Angioseal collagen plaque. A) Insertion of the snare catheter (Sn) along the guidewire in the common femoral artery (CFA). B) Unfolding the loops beyond the Angioseal collagen plaque (c) in the superficial femoral artery (SFA). C) Retrieval of the captured plaque (c) with the snare catheter (Sn). PFA = Profound femoral artery